A rare case of pouched Schistosomus reflexus in a crossbred cow - Prakash, S; Prabaharan, V; Raja, S; Satheshkumar, S (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A rare case of pouched schistosomus reflexus in a Holstein Friesian crossbred cow, which was delivered per vaginum by mutation operation is reported.